2007
DOI: 10.1071/en06065
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the cycling of dimethylsulfide and dimethylsulfoniopropionate in coral reef waters of the Great Barrier Reef

Abstract: Environmental context. Levels of atmospheric dimethylsulfide (DMS) and its oxidation products are reputed to affect the microphysics of clouds and the amount of incoming solar radiation to the ocean. Studies of DMS and its precursor compound dimethylsulfoniopropionate (DMSP) at two inshore fringing coral reefs in the Great Barrier Reef highlight pronounced seasonal, diurnal and tidal variation of these compounds, with dissolved DMS and DMSP significantly correlated with sea surface temperatures (SSTs) up to 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
105
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(121 citation statements)
references
References 42 publications
13
105
2
1
Order By: Relevance
“…However, the coral only releases a fraction of this as we have estimated that the % of S (DMS + DMSP) expelled from Acropora spp. each day is 0.2-0.4% of the total available pool (Jones et al, 2007). This is in agreement with estimates of zooxanthellae released from A. formosa (Hoegh-Guldberg and Smith, 1989;Jones, 1995) and strongly suggests that monitoring organosulphur production from corals in chamber experiments is a good indicator of zooxanthellae expulsion and coral stress (Jones et al, 2007).…”
Section: Storage and Analysis Of Seawater Dmspsupporting
confidence: 71%
See 3 more Smart Citations
“…However, the coral only releases a fraction of this as we have estimated that the % of S (DMS + DMSP) expelled from Acropora spp. each day is 0.2-0.4% of the total available pool (Jones et al, 2007). This is in agreement with estimates of zooxanthellae released from A. formosa (Hoegh-Guldberg and Smith, 1989;Jones, 1995) and strongly suggests that monitoring organosulphur production from corals in chamber experiments is a good indicator of zooxanthellae expulsion and coral stress (Jones et al, 2007).…”
Section: Storage and Analysis Of Seawater Dmspsupporting
confidence: 71%
“…DMSP contributions from the coral host are also possible . However, in our view the major fraction of DMSP released into the chamber is from expelled zooxanthellae (Jones et al, 2007). For example, A. intermedia in this study contained 1.2 × 10 6 cells per cm 2 of coral surface area and the cellular concentration of unbleached A. intermedia contained~147 fmol cell −1 .…”
Section: Storage and Analysis Of Seawater Dmspmentioning
confidence: 96%
See 2 more Smart Citations
“…In corals, bleached colonies of Acropora formosa show significantly greater DMSP concentrations per zooxanthellae (436 fmol cell -1 ) than in unbleached colonies (171 fmol cell -1 ) (Broadbent et al 2002). Jones et al (2007) also reported significant DMS and DMSP correlations with sea surface temperatures up to 30°C. While the above-mentioned observations suggest a potential link between DMSP production and photophysiological stress, there have, however, been no studies characterizing how DMSP in corals might vary along a photosynthetic (light) gradient that exposes corals to varying amounts of solar radiation and cellular oxidative stress.…”
Section: Introductionmentioning
confidence: 94%